Kewenangan dalam Penerapan Pengaturan Analisis Dampak Lalu Lintas (Andalalin) - Feri Prasetyo (Universitas Muhammadiyah Sidoarjo, 2016)
Traffic Impact Analysis (Andalalin) as a special study on the construction of any buildings and other land use of the city's transportation system, especially the road network in the building. In order to support it, hotels, malls and so on were built. Along with those development would lead to changes in land use, for example, change of land designation that turned into centers of activity. Implementation traffic impact analysis (andalalin) in Sidoarjo did not maximal yet. There are some weaknesses, namely the gap between legislation and implementation. Residential areas with a density high enough such as offices, shops and trade, hotels, hospitals, schools, industrial and sports stadiums. This problem can be solved by traffic impact analysis prior to the issuance of building permits (IMB) and some were after. In addition, traffic management as an approach also be designed to deal with the impact of the trip was awakened to the existing road network.